Marketing bank services to youth in China. Issue 3 (21st August 2017) - Chan, Kara; Tsang, Lennon; Chen, Jie
Abstract : Purpose: The purpose of this paper is to explore the banking experiences and awareness of marketing efforts of banks among youth in mainland China. Design/methodology/approach: Four focus-group interviews were conducted. A convenience sample of 26 participants aged 17 to 20 years was recruited in Laiwu, Shandong, a medium-sized city in China. They were asked to report experiences that could illustrate good and bad banking services. They were also asked to recall bank marketing promotions. Findings: Participants' perceived service quality of banks was determined by staff attitude, service delivery, physical environment and comparison of user experience. The marketing communication activities they recalled most frequently included product placements, advertising slogans, entertaining commercials and co-branding with online games. Research limitations/implications: The findings were based on a non-probability sample. The study also did not differentiate between personal experience and indirect experience with family and friends. Similar studies can be conducted in large cities or in rural China to compare banking experiences in different social economic settings. Further studies can be designed using quantitative methodology to measure the importance of various factors in influencing perceptions of service quality. Online banking experience can also be studied in the future. Practical implications: Banks in China can enhance their competitiveness and brand reputation through raising the professionalism of their front-line staff, improving efficiency and transparency and streamlining the service process. Banks can make contacts with youth through offline and online promotional activities, such as co-branding with popular online games. Originality/value: This is the first study on banking services among youth conducted in a medium-sized city in China.